Sistema de gestión de calidad y mejora de la administración operación y mantenimiento del sistema JURECH - Cali Gadvay, Robinson Javier (2025)
In today's dynamic environment, globalization, economic instability, and evolving customer needs necessitate more competitive organizations. To secure their client base and seek new opportunities, businesses find it necessary to implement management tools that enhance processes, minimize deviations, and boost productivity. One such crucial tool is the implementation of a Quality Management System and the improvement of the Administration, Operation, and Maintenance of the JURECH System, which ensures a systematic process approach. A foundational element of any Quality Management System is a robust documentation system, which clarifies the What, How, Who, and When of key activities impacting product or service quality. This feasible project research, leveraging bibliographic-documentary analysis and a descriptive design, proposes enhancements to quality management. Clear general and specific objectives were established, employing a hypothetico-deductive methodology to derive specific conclusions from generalized information. A survey with a questionnaire, administered to a sample of 372 cases, helped to understand the current situation. From this analysis, the development of a proposal and the presentation of significant results derived from this research were proposed. Chapter 1 introduces the topic, problem statement, context, and research objectives. Chapter 2 reviews relevant background and theoretical foundations. Chapter 3 details the research method, including study type, design, techniques, instruments, population, and sample. Chapter 4 presents the analysis and discussion of results, alongside hypothesis verification. Chapter 5 offers conclusions and recommendations derived from the findings. Finally, Chapter 6 outlines proposed strategies and their expected implementation outcomes.